A boron-containing crosslinking agent for thermoplastic polyurethane elastomers, and a preparation method and applications thereof
Patent Information
- Application Number
- CN202311717683.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-13
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-12-13
AI Technical Summary
Existing thermoplastic polyurethane elastomers (TPUs) suffer from low strength and low toughness in terms of mechanical properties, which limits their further application in many fields, and existing reinforcement methods often reduce their ductility and toughness.
A boron-containing crosslinking agent is used to prepare the crosslinking agent by reacting polyethyleneimine with phenylboronic acid compounds containing aldehyde groups. The crosslinking agent is then crosslinked with thermoplastic polyurethane elastomer to form dynamic coordination bonds, thereby improving the strength and toughness of the material.
It significantly improves the toughness and strength of TPU, with an elongation of 950% and a tensile strength of 7.95 MPa. At the same time, it does not affect the thermoplasticity of the material at high temperatures, making it suitable for industrial applications.
Smart Images

Figure CN117700730B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials processing, specifically relating to a boron-containing crosslinking agent for thermoplastic polyurethane elastomers, its preparation method, and its application. Background Technology
[0002] Polyurethane is a versatile polymer applicable to numerous fields. Among them, thermoplastic polyurethane elastomer (TPU) possesses excellent comprehensive properties and processing characteristics, including oil resistance, abrasion resistance, and aging resistance, making it suitable for applications in footwear, transportation, tires, construction, machinery, electronics, and biomedicine. However, with the continuous advancement of modern science and the increasing global demand for high-performance materials, the low strength and low toughness of TPU limit its further development and application.
[0003] Currently, strategies for improving the mechanical properties of TPU mainly include polymer / filler hybridization (ACS Nano 2009, 3, 1564) and molecular structure design (Advanced Materials 2021, 33, 2101498; Journal of Materials Chemistry A 2021, 9, 20737). Polymer hybridization can enhance TPU, but it also reduces its ductility and toughness, and compatibility with the matrix needs to be considered. Molecular structure design can significantly enhance TPU, but it involves complex monomers and structures, which is not conducive to mass production and industrial applications.
[0004] Therefore, there is an urgent need to design a new method that can not only improve the strength and toughness of TPU materials at the same time, but also be suitable for mass production and industrial applications. Summary of the Invention
[0005] The present invention aims to provide a boron-containing crosslinking agent, and another objective is to provide a boron-containing crosslinking agent, its preparation method, and its application.
[0006] The present invention provides a boron-containing crosslinking agent, wherein the raw materials of the boron-containing crosslinking agent include: polyethyleneimine and phenylboronic acid compounds with aldehyde groups; the mass ratio of the polyethyleneimine and the phenylboronic acid compounds with aldehyde groups is (0.1-10):(1-5).
[0007] Furthermore,
[0008] The molecular weight of the polyethyleneimine is 100-10000 g / mol;
[0009] The mass ratio of the polyethyleneimine to the phenylboronic acid compound is (0.5-2):(1-5).
[0010] Furthermore,
[0011] The mass ratio of the polyethyleneimine to the phenylboronic acid compound is 1:1;
[0012] The molecular weight of the polyethyleneimine is 300-600 g / mol;
[0013] The phenylboronic acid compound with an aldehyde group is any one or more of 4-formylphenylboronic acid, 2-formylphenylboronic acid, 4-formyl-2-methylphenylboronic acid, (4-formyl-3-methylphenyl)boronic acid, 4-formylnaphthalene-1-boronic acid, (4-formyl-3-methoxyphenyl)boronic acid, 4-fluoro-2-aldehyde phenylboronic acid, 4-fluoro-3-aldehyde phenylboronic acid, 3-fluoro-4-aldehyde phenylboronic acid, 2-fluoro-5-aldehyde phenylboronic acid, 2-fluoro-4-aldehyde phenylboronic acid, 4-chloro-2-aldehyde phenylboronic acid, 2-chloro-5-aldehyde phenylboronic acid, 4-benzyloxy-2-aldehyde phenylboronic acid, 2,6-difluoro-3-aldehyde phenylboronic acid, 3,4-difluoro-2-aldehyde phenylboronic acid, and 4-formyl-3-trifluoromethylphenylboronic acid; preferably 4-formylphenylboronic acid.
[0014] The present invention also provides a method for preparing the above-mentioned boron-containing crosslinking agent, the method comprising the following steps:
[0015] (1) Polyethyleneimine and phenylboronic acid compounds with aldehyde groups are dissolved in organic solvents to obtain polyethyleneimine solution and phenylboronic acid compound solution with aldehyde groups.
[0016] (2) The polyethyleneimine solution obtained in step (1) is mixed with the phenylboronic acid compound solution with aldehyde group and reacted to obtain the product.
[0017] The present invention also provides a composite material, which is prepared from thermoplastic polyurethane elastomer and the above-mentioned boron-containing crosslinking agent as raw materials;
[0018] The mass ratio of the thermoplastic polyurethane elastomer to the boron-containing crosslinking agent is (1-10):(0.05-0.25).
[0019] Furthermore,
[0020] The mass ratio of the thermoplastic polyurethane elastomer to the boron-containing crosslinking agent is 5:(0.05-0.25), preferably 5:0.15.
[0021] The raw materials for the thermoplastic polyurethane elastomer include polytetrahydrofuran, diisocyanate, and pyridine compounds;
[0022] The mass ratio of the polytetrahydrofuran, diisocyanate and pyridine compound is (1-20):(0.5-5):(0.1-2), preferably 10:1.68:0.55.
[0023] Furthermore,
[0024] The raw materials for the thermoplastic polyurethane elastomer also include a catalyst, wherein the catalyst is dibutyltin dilaurate;
[0025] The diisocyanate is any one or more of naphthalene diisocyanate, terephthalic diisocyanate, toluene diisocyanate, isophorone diisocyanate, trimethylhexane diisocyanate, 1,6-hexane diisocyanate, and 4,4-diphenylmethane diisocyanate.
[0026] The pyridine compound is any one or more of 2,6-diaminopyridine, 2,4-diaminopyridine, 2,5-diaminopyridine, 2,3-diaminopyridine, and 3,4-diaminopyridine.
[0027] Furthermore,
[0028] The diisocyanate is 1,6-hexamethylene diisocyanate; the pyridine compound is 3,4-diaminopyridine.
[0029] The present invention also provides a method for using the above-mentioned composite material, the method comprising the following steps:
[0030] (1) Polytetrahydrofuran, diisocyanate and pyridine compounds are dissolved in organic solvent A and reacted to obtain thermoplastic polyurethane elastomer;
[0031] (2) Dissolve the thermoplastic polyurethane elastomer obtained in step (1) in organic solvent A to obtain solution A, and dissolve the boron-containing crosslinking agent mentioned above in organic solvent B to obtain solution B;
[0032] (3) Mix solution A and solution B and react to obtain a composite material.
[0033] In steps (1) and (2), organic solvent A is any one or both of tetrahydrofuran and N,N-dimethylformamide, preferably tetrahydrofuran;
[0034] In steps (2) and (3), organic solvent B is any one or both of methanol and dimethyl sulfoxide, preferably methanol.
[0035] The present invention also provides applications of the above-mentioned composite material in the aerospace, automotive manufacturing, footwear and leather industry, and sports industry.
[0036] Benzylboronic acid compounds are compounds whose molecules contain phenyl and boric acid groups.
[0037] This invention prepares a boron-containing crosslinking agent by reacting polyethyleneimine with an aldehyde-containing phenylboronic acid compound. This crosslinking agent is then used to crosslink TPU prepared using polytetrahydrofuran, 1,6-hexamethylene diisocyanate, and 3,4-diaminopyridine to obtain the TPU composite material of this invention. Compared with commercially available boron-containing crosslinking agents, the TPU composite material of this invention exhibits significantly improved toughness and strength, with Example 6 showing the best performance, achieving an elongation of 950% and a tensile strength of 7.95 MPa. Furthermore, the boron-containing crosslinking agent of this invention forms dynamic coordination bonds, which can dissociate at high temperatures without affecting the thermoplasticity of the TPU. The TPU composite material of this invention possesses high strength and high toughness, and has broad application prospects in the aerospace, automotive, footwear, and sports industries.
[0038] Obviously, based on the above description of the present invention, and according to common technical knowledge and conventional methods in the field, various other modifications, substitutions or alterations can be made without departing from the basic technical concept of the present invention.
[0039] The following detailed embodiments further illustrate the above-described content of the present invention. However, this should not be construed as limiting the scope of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention. Attached Figure Description
[0040] Figure 1 The image shows the hydrogen nuclear magnetic resonance spectrum of the boron-containing crosslinking agent prepared in this invention.
[0041] Figure 2 The infrared spectrum of the boron-containing crosslinking agent prepared in this invention is shown.
[0042] Figure 3 The stress-strain curves are for Examples 5, 6, 7 and Comparative Example 1.
[0043] Figure 4 The mechanical strength diagrams are for Example 6 and Comparative Examples 1, 2, 3, and 4. Detailed Implementation
[0044] The raw materials and equipment used in this invention are all known products, obtained by purchasing commercially available products.
[0045] Example 1: Preparation of the boron-containing crosslinking agent of the present invention
[0046] Table 1. Raw materials and process parameters of boron-containing crosslinking agents in Examples 1-4 of the present invention.
[0047]
[0048] 0.9 g of polyethyleneimine with a molecular weight of 300 g / mol was dissolved in 2 g of anhydrous methanol, and 0.9 g of 4-formylphenylboronic acid was dissolved in 5 g of anhydrous methanol to prepare homogeneous polyethyleneimine and 4-formylphenylboronic acid solutions, respectively. These homogeneous solutions were added to a deoxygenated, sealed three-necked flask equipped with a magnetic stirrer. The reaction system was protected by argon gas and reacted at 25°C for 24 h to obtain a reaction solution. The reaction solution was precipitated by adding excess anhydrous ethyl acetate, filtered to obtain a solid product, and the precipitate was dissolved in anhydrous methanol and precipitated again with anhydrous ethyl acetate. This process was repeated three times to remove unreacted raw materials. The final product was then dried in a vacuum oven at 35°C to constant weight to obtain the final product, a novel boron-containing crosslinking agent for TPU.
[0049] Example 2: Preparation of the boron-containing crosslinking agent of the present invention
[0050] 0.9 g of polyethyleneimine with a molecular weight of 300 g / mol was dissolved in 4 g of anhydrous methanol, and 0.9 g of 4-formylphenylboronic acid was dissolved in 6 g of anhydrous methanol to prepare homogeneous polyethyleneimine and 4-formylphenylboronic acid solutions, respectively. These homogeneous solutions were added to a deoxygenated, sealed three-necked flask equipped with a magnetic stirrer. The reaction system was protected by argon gas and reacted at 25°C for 24 h to obtain a reaction solution. The reaction solution was then precipitated by adding excess anhydrous ethyl acetate. The solid product was obtained by filtration, and the precipitate was dissolved in anhydrous methanol and precipitated again with anhydrous ethyl acetate. This process was repeated three times to remove unreacted raw materials. The final product was then dried in a vacuum oven at 35°C to constant weight to obtain the final product, a novel boron-containing crosslinking agent for TPU.
[0051] Example 3: Preparation of the boron-containing crosslinking agent of the present invention
[0052] 0.9 g of polyethyleneimine with a molecular weight of 600 g / mol was dissolved in 2 g of anhydrous methanol, and 0.9 g of 4-formylphenylboronic acid was dissolved in 5 g of anhydrous methanol to prepare homogeneous polyethyleneimine and 4-formylphenylboronic acid solutions, respectively. These homogeneous solutions were added to a deoxygenated, sealed three-necked flask equipped with a magnetic stirrer. The reaction system was protected by argon gas and reacted at 25°C for 24 h to obtain a reaction solution. The reaction solution was then precipitated by adding excess anhydrous ethyl acetate. The solid product was obtained by filtration, and the precipitate was dissolved in anhydrous methanol and precipitated again with anhydrous ethyl acetate. This process was repeated three times to remove unreacted raw materials. The final product, a novel boron-containing crosslinking agent for TPU, was then dried in a vacuum oven at 35°C to constant weight.
[0053] Example 4: Preparation of the boron-containing crosslinking agent of the present invention
[0054] 0.9 g of polyethyleneimine with a molecular weight of 300 g / mol was dissolved in 2 g of anhydrous methanol, and 0.9 g of 4-formylphenylboronic acid was dissolved in 5 g of anhydrous methanol to prepare homogeneous polyethyleneimine and 4-formylphenylboronic acid solutions, respectively. These homogeneous solutions were added to a deoxygenated, sealed three-necked flask equipped with a magnetic stirrer. The reaction system was protected by argon gas and reacted at 35 °C for 24 h to obtain a reaction solution. The reaction solution was then precipitated by adding excess anhydrous ethyl acetate. The solid product was obtained by filtration, and the precipitate was dissolved in anhydrous methanol and precipitated again with anhydrous ethyl acetate. This process was repeated three times to remove unreacted raw materials. The final product, a novel boron-containing crosslinking agent for TPU, was then dried in a vacuum oven at 35 °C to constant weight.
[0055] Example 5: Preparation of the TPU composite material of the present invention
[0056] Table 2. Raw materials of Examples 5-7 and Comparative Examples 1-4 of the present invention.
[0057]
[0058]
[0059] The steps for preparing the novel boron-containing crosslinking agent for TPU are the same as in Example 1.
[0060] 10 g of polytetrahydrofuran (molecular weight approximately 2000 g / mol) was added to a 100 mL three-necked flask equipped with a magnetic stirrer and connected to a reflux condenser. The mixture was evacuated at 120 °C for 1 h to remove water from the reaction system and the polytetrahydrofuran. Then, argon gas was introduced for protection, and the temperature was lowered to 60 °C. A homogeneous solution was prepared by dissolving 1.68 g of 1,6-hexamethylene diisocyanate, 0.55 g of 3,4-diaminopyridine, and 0.03 g of catalyst (dibutyltin dilaurate) in 15 mL of anhydrous tetrahydrofuran. This solution was added to the aforementioned sealed three-necked flask, and the mixture was stirred at 60 °C for 6 h. The resulting solid product was dried in a vacuum oven to constant weight to obtain thermoplastic polyurethane elastomer.
[0061] 5g of the obtained thermoplastic polyurethane elastomer was dissolved in 30mL of tetrahydrofuran to obtain a TPU solution. 0.05g of the boron-containing crosslinking agent prepared in Example 1 was dissolved in 2mL of methanol. The boron-containing crosslinking agent solution and the TPU solution were then mixed evenly. The resulting homogeneous solution was poured into a PTFE mold and allowed to evaporate at room temperature. Two days later, it was placed in a vacuum oven and dried at 55°C to constant weight to obtain the novel boron-containing crosslinked TPU.
[0062] Example 6: Preparation of the TPU composite material of the present invention
[0063] The steps for preparing the novel boron-containing crosslinking agent for TPU are the same as in Example 1.
[0064] 10 g of polytetrahydrofuran (Mn approximately 2000) was added to a 100 mL three-necked flask equipped with a magnetic stirrer and connected to a reflux condenser. The mixture was evacuated at 120 °C for 1 h to remove water from the reaction system and the polytetrahydrofuran. Then, argon gas was introduced for protection, and the temperature was lowered to 60 °C. A homogeneous solution was prepared by dissolving 1.68 g of 1,6-hexamethylene diisocyanate, 0.55 g of 3,4-diaminopyridine, and 0.03 g of catalyst (dibutyltin dilaurate) in 15 mL of anhydrous tetrahydrofuran. This solution was added to the aforementioned sealed three-necked flask, and the mixture was stirred at 60 °C for 6 h. The resulting solid product was dried in a vacuum oven to constant weight to obtain thermoplastic polyurethane elastomer.
[0065] 5g of the obtained thermoplastic polyurethane elastomer was dissolved in 30mL of tetrahydrofuran to obtain a TPU solution. 0.15g of the boron-containing crosslinking agent prepared in Example 1 was dissolved in 3mL of methanol. The boron-containing crosslinking agent solution was then mixed thoroughly with the TPU solution. The resulting homogeneous solution was poured into a PTFE mold and allowed to evaporate at room temperature. Two days later, it was placed in a vacuum oven and dried at 55°C to constant weight to obtain the novel boron-containing crosslinked TPU.
[0066] Example 7: Preparation of the TPU composite material of the present invention
[0067] The steps for preparing the novel boron-containing crosslinking agent for TPU are the same as in Example 1.
[0068] 10 g of polytetrahydrofuran (Mn approximately 2000) was added to a 100 mL three-necked flask equipped with a magnetic stirrer and connected to a reflux condenser. The mixture was evacuated at 120 °C for 1 h to remove water from the reaction system and the polytetrahydrofuran. Then, argon gas was introduced for protection, and the temperature was lowered to 60 °C. A homogeneous solution was prepared by dissolving 1.68 g of 1,6-hexamethylene diisocyanate, 0.55 g of 3,4-diaminopyridine, and 0.03 g of catalyst (dibutyltin dilaurate) in 15 mL of anhydrous tetrahydrofuran. This solution was added to the aforementioned sealed three-necked flask, and the mixture was stirred at 60 °C for 6 h. The resulting solid product was dried in a vacuum oven to constant weight to obtain thermoplastic polyurethane elastomer.
[0069] 5g of the obtained thermoplastic polyurethane elastomer was dissolved in 30mL of tetrahydrofuran to obtain a TPU solution. 0.25g of the boron-containing crosslinking agent prepared in Example 1 was dissolved in 5mL of methanol. The boron-containing crosslinking agent solution was then mixed thoroughly with the TPU solution. The resulting homogeneous solution was poured into a PTFE mold and allowed to evaporate at room temperature. Two days later, it was placed in a vacuum oven and dried at 55°C to constant weight to obtain the novel boron-containing crosslinked TPU.
[0070] Comparative Example 1: Preparation of TPU without boron-containing crosslinking agent
[0071] 10 g of polytetrahydrofuran (Mn approximately 2000) was added to a 100 mL three-necked flask equipped with a magnetic stirrer and connected to a reflux condenser. The mixture was evacuated at 120 °C for 1 h to remove water from the reaction system and the polytetrahydrofuran. Then, argon gas was introduced for protection, and the temperature was lowered to 60 °C. A homogeneous solution was prepared by dissolving 1.68 g of 1,6-hexamethylene diisocyanate, 0.55 g of 3,4-diaminopyridine, and 0.03 g of catalyst (dibutyltin dilaurate) in 15 mL of anhydrous tetrahydrofuran. This solution was added to the aforementioned sealed three-necked flask, and the mixture was stirred at 60 °C for 6 h. The resulting solid product was dried in a vacuum oven to constant weight to obtain thermoplastic polyurethane elastomer.
[0072] Take 5g of the obtained thermoplastic polyurethane elastomer and dissolve it in tetrahydrofuran without adding the boron-containing crosslinking agent prepared in Example 1. Pour the solution into a PTFE mold and wait for the solvent to evaporate at room temperature. Two days later, place it in a vacuum oven and dry it at 55°C to constant weight to obtain TPU without boron-containing crosslinking agent crosslinking.
[0073] Comparative Example 2: Preparation of TPU crosslinked with boric acid as a boron-containing crosslinking agent
[0074] 10 g of polytetrahydrofuran (Mn approximately 2000) was added to a 100 mL three-necked flask equipped with a magnetic stirrer and connected to a reflux condenser. The mixture was evacuated at 120 °C for 1 h to remove water from the reaction system and the polytetrahydrofuran. Then, argon gas was introduced for protection, and the temperature was lowered to 60 °C. A homogeneous solution was prepared by dissolving 1.68 g of 1,6-hexamethylene diisocyanate, 0.55 g of 3,4-diaminopyridine, and 0.03 g of catalyst (dibutyltin dilaurate) in 15 mL of anhydrous tetrahydrofuran. This solution was added to the aforementioned sealed three-necked flask, and the mixture was stirred at 60 °C for 6 h. The resulting solid product was dried in a vacuum oven to constant weight to obtain thermoplastic polyurethane elastomer.
[0075] Dissolve 5g of the obtained thermoplastic polyurethane elastomer in tetrahydrofuran, and dissolve 0.15g of boric acid (boron crosslinking agent) in methanol. Mix the resulting solution with the TPU solution until homogeneous. Pour the homogeneous mixture into a PTFE mold and allow the solvent to evaporate at room temperature. After two days, place the mixture in a vacuum oven and dry it at 55°C until constant weight to obtain TPU crosslinked with boric acid as the boron crosslinking agent.
[0076] Comparative Example 3: Preparation of TPU crosslinked with borax as a boron-containing crosslinking agent
[0077] 10 g of polytetrahydrofuran (Mn approximately 2000) was added to a 100 mL three-necked flask equipped with a magnetic stirrer and connected to a reflux condenser. The mixture was evacuated at 120 °C for 1 h to remove water from the reaction system and the polytetrahydrofuran. Then, argon gas was introduced for protection, and the temperature was lowered to 60 °C. A homogeneous solution was prepared by dissolving 1.68 g of 1,6-hexamethylene diisocyanate, 0.55 g of 3,4-diaminopyridine, and 0.03 g of catalyst (dibutyltin dilaurate) in 15 mL of anhydrous tetrahydrofuran. This solution was added to the aforementioned sealed three-necked flask, and the mixture was stirred at 60 °C for 6 h. The resulting solid product was dried in a vacuum oven to constant weight to obtain thermoplastic polyurethane elastomer.
[0078] Dissolve 5g of the obtained thermoplastic polyurethane elastomer in tetrahydrofuran, and dissolve 0.15g of borax (a boron-containing crosslinking agent) in methanol. Mix the resulting solution with the TPU solution until homogeneous. Pour the homogeneous mixture into a PTFE mold and allow the solvent to evaporate at room temperature. After two days, place the mixture in a vacuum oven and dry it at 55°C until constant weight to obtain TPU crosslinked with borax as a boron-containing crosslinking agent.
[0079] Comparative Example 4: Preparation of TPU crosslinked with commercial organoboron crosslinking agent A
[0080] 10 g of polytetrahydrofuran (Mn approximately 2000) was added to a 100 mL three-necked flask equipped with a magnetic stirrer and connected to a reflux condenser. The mixture was evacuated at 120 °C for 1 h to remove water from the reaction system and the polytetrahydrofuran. Then, argon gas was introduced for protection, and the temperature was lowered to 60 °C. A homogeneous solution was prepared by dissolving 1.68 g of 1,6-hexamethylene diisocyanate, 0.55 g of 3,4-diaminopyridine, and 0.03 g of catalyst (dibutyltin dilaurate) in 15 mL of anhydrous tetrahydrofuran. This solution was added to the aforementioned sealed three-necked flask, and the mixture was stirred at 60 °C for 6 h. The resulting solid product was dried in a vacuum oven to constant weight to obtain thermoplastic polyurethane elastomer.
[0081] Dissolve 5g of the obtained thermoplastic polyurethane elastomer in tetrahydrofuran, and dissolve 0.15g of commercial organoboron crosslinking agent A in methanol. Mix the solutions of both solutions thoroughly with the TPU solution. Pour the resulting homogeneous solution into a PTFE mold and allow the solvent to evaporate at room temperature. After two days, place the mixture in a vacuum oven and dry it at 55°C until constant weight to obtain the TPU crosslinked with organoboron crosslinking agent A.
[0082] Commercial organoboron crosslinking agent A was purchased from Tianjin Binhai New Area Dagang Fangyuan Drilling and Mining Technology Service Co., Ltd., with product number BCL-35.
[0083] The following experimental examples demonstrate the beneficial effects of the present invention.
[0084] Structural characterization of the boron-containing crosslinking agent prepared in Experimental Example 1 and Example 1 of the present invention
[0085] I. Experimental Methods
[0086] The proton NMR spectrum of the boron-containing crosslinking agent was obtained using an Advance III HD 400MHz spectrometer (Bruker) instrument, with CD3OD as the deuterated reagent.
[0087] The Fourier transform infrared spectra of the boron-containing crosslinking agent were obtained using a Thermo Scientific Nicoleti S50 FTIR instrument in transmission mode.
[0088] II. Experimental Results
[0089] From the proton NMR spectrum of the boron-containing crosslinking agent (i.e. Figure 1 As can be seen, a characteristic peak appears at a chemical shift of approximately 8.3 ppm. This characteristic peak is the vibrational peak of hydrogen in the -CH=N- (imine bond) (Polym. Chem., 2020, 11, 2585), indicating that the amino group in polyethyleneimine and the aldehyde group in phenylboronic acid with an aldehyde group have successfully reacted to form an imine bond, thus successfully synthesizing a boron-containing crosslinking agent. Simultaneously, from the infrared spectrum of the boron-containing crosslinking agent (… Figure 2 The same result can also be obtained; the infrared spectrum of the boron-containing crosslinking agent is at approximately 1643 cm⁻¹. -1 A new characteristic peak appears at this point, which is the stretching vibration peak of C=N.
[0090] Experimental Example 2: Tensile strength and elongation of TPU crosslinked with boron-containing crosslinking agent of the present invention.
[0091] I. Experimental Methods
[0092] The mechanical properties of the TPU crosslinked with boron-containing crosslinking agent of this invention were tested by uniaxial tensile testing, which was conducted on a CMT4503 general-purpose tensile testing machine at a tensile rate of 500 mm / min. The samples were cut using a dumbbell-shaped cutter, and all samples were of uniform size. The dimensions of the narrow neck portion of the sample were 18 mm in length and 2 mm in width.
[0093] II. Experimental Results
[0094] Table 3 shows the elongation and tensile strength results for Examples 5-7 and Comparative Examples 1-4.
[0095] sample Elongation % Tensile strength (MPa) Example 5 766±93 5.64±0.63 Example 6 940±139 7.89±1.39 Example 7 454±127 6.32±0.74 Comparative Example 1 655±121 5.41±0.22 Comparative Example 2 606±78 6.07±0.78 Comparative Example 3 638±64 5.98±0.64 Comparative Example 4 640±86 5.75±0.86
[0096] The experimental results are shown in Table 3. The elongation and tensile strength results of Examples 5-7 and Comparative Example 1 are as follows: Figure 3As shown, the tensile strength results of Example 6 and Comparative Examples 1-4 are as follows: Figure 4 As shown.
[0097] It can be seen that the TPU composite material of Example 6 has higher and better tensile strength and elongation. Compared with the TPU prepared in Comparative Example 1 without using a boron-containing crosslinking agent, the tensile strength is increased by 45.8%. Even compared with TPUs compounded with commonly used boron crosslinking agents (boric acid, borax, commercial organoboron crosslinking agent A), i.e., Comparative Examples 2-4, the TPU composite material prepared in Example 6 of this invention has the best elongation and tensile strength. The elongation and tensile strength of the TPU composite material prepared in Example 6 are much higher than those of the other examples and Comparative Examples 1-4.
[0098] Experimental results show that the TPU obtained by crosslinking with the boron-containing crosslinking agent of the present invention has excellent elongation and tensile strength. Among them, Example 6 has the best elongation and tensile strength, which are 950% and 7.93 MPa, respectively, which are much higher than the other examples and comparative examples 1-4.
[0099] This invention prepares a boron-containing crosslinking agent by reacting polyethyleneimine with an aldehyde-containing phenylboronic acid compound. This crosslinking agent is then used to crosslink TPU prepared using polytetrahydrofuran, 1,6-hexamethylene diisocyanate, and 3,4-diaminopyridine to obtain the TPU composite material of this invention. Compared with commercially available boron-containing crosslinking agents, the TPU composite material of this invention exhibits significantly improved toughness and strength, with Example 6 showing the best performance, achieving an elongation of 950% and a tensile strength of 7.95 MPa. Furthermore, the boron-containing crosslinking agent of this invention forms dynamic coordination bonds, which can dissociate at high temperatures without affecting the thermoplasticity of the TPU. The TPU composite material of this invention possesses high strength and high toughness, and has broad application prospects in the aerospace, automotive, footwear, and sports industries.
Claims
1. A composite material, characterized in that, The composite material is prepared from thermoplastic polyurethane elastomer and boron-containing crosslinking agent as raw materials; The mass ratio of the thermoplastic polyurethane elastomer to the boron-containing crosslinking agent is (1-10):(0.05-0.25); The raw materials for the boron-containing crosslinking agent include: polyethyleneimine and phenylboronic acid compounds with aldehyde groups; the mass ratio of polyethyleneimine to phenylboronic acid compounds with aldehyde groups is (0.1-10):(1-5).
2. The composite material as described in claim 1, characterized in that, The molecular weight of the polyethyleneimine is 100-10000 g / mol; The mass ratio of the polyethyleneimine to the phenylboronic acid compound is (0.5-2):(1-5).
3. The composite material as described in claim 2, characterized in that, The mass ratio of the polyethyleneimine to the phenylboronic acid compound is 1:1; The molecular weight of the polyethyleneimine is 300-600 g / mol; The phenylboronic acid compounds with aldehyde groups are any one or more of the following: 4-formylphenylboronic acid, 2-formylphenylboronic acid, 4-formyl-2-methylphenylboronic acid, (4-formyl-3-methylphenyl)boronic acid, (4-formyl-3-methoxyphenyl)boronic acid, 4-fluoro-2-aldehyde phenylboronic acid, 4-fluoro-3-aldehyde phenylboronic acid, 3-fluoro-4-aldehyde phenylboronic acid, 2-fluoro-5-aldehyde phenylboronic acid, 2-fluoro-4-aldehyde phenylboronic acid, 4-chloro-2-aldehyde phenylboronic acid, 2-chloro-5-aldehyde phenylboronic acid, 4-benzyloxy-2-aldehyde phenylboronic acid, 2,6-difluoro-3-aldehyde phenylboronic acid, 3,4-difluoro-2-aldehyde phenylboronic acid, and 4-formyl-3-trifluoromethylphenylboronic acid.
4. The composite material as described in claim 3, characterized in that, The phenylboronic acid compound with an aldehyde group is 4-formylphenylboronic acid.
5. The composite material according to any one of claims 1-4, characterized in that, The preparation method of the boron-containing crosslinking agent includes the following steps: (1) Polyethyleneimine and phenylboronic acid compounds with aldehyde groups are dissolved in organic solvents to obtain polyethyleneimine solution and phenylboronic acid compound solution with aldehyde groups; (2) The polyethyleneimine solution obtained in step (1) is mixed with the phenylboronic acid compound solution with aldehyde group and reacted to obtain the product.
6. The composite material as described in claim 1, characterized in that, The mass ratio of the thermoplastic polyurethane elastomer to the boron-containing crosslinking agent is 5:(0.05-0.25); The raw materials for the thermoplastic polyurethane elastomer include polytetrahydrofuran, diisocyanate, and pyridine compounds; The mass ratio of polytetrahydrofuran, diisocyanate and pyridine compound is (1-20):(0.5-5):(0.1-2).
7. The composite material as described in claim 6, characterized in that, The mass ratio of the thermoplastic polyurethane elastomer to the boron-containing crosslinking agent is 5:0.15; The mass ratio of the polytetrahydrofuran, diisocyanate, and pyridine compound is 10:1.68:0.
55.
8. The composite material as described in claim 6 or 7, characterized in that, The raw materials for the thermoplastic polyurethane elastomer also include a catalyst, wherein the catalyst is dibutyltin dilaurate; The diisocyanate is any one or more of naphthalene diisocyanate, terephthalic diisocyanate, toluene diisocyanate, isophorone diisocyanate, trimethylhexane diisocyanate, 1,6-hexane diisocyanate, and 4,4-diphenylmethane diisocyanate. The pyridine compound is any one or more of 2,6-diaminopyridine, 2,4-diaminopyridine, 2,5-diaminopyridine, 2,3-diaminopyridine, and 3,4-diaminopyridine.
9. The composite material as described in claim 8, characterized in that, The diisocyanate is 1,6-hexamethylene diisocyanate; the pyridine compound is 3,4-diaminopyridine.
10. A method for preparing the composite material according to any one of claims 1-9, the method comprising the following steps: (1) Polytetrahydrofuran, diisocyanate and pyridine compounds are dissolved in organic solvent A and reacted to obtain thermoplastic polyurethane elastomer; Alternatively, polytetrahydrofuran, diisocyanate, pyridine compounds and catalyst are dissolved in organic solvent A and reacted to obtain thermoplastic polyurethane elastomer; (2) Dissolve the thermoplastic polyurethane elastomer obtained in step (1) in organic solvent A to obtain solution A, and dissolve the boron-containing crosslinking agent in organic solvent B to obtain solution B; (3) Mix solution A and solution B and react to obtain a composite material; In steps (1) and (2), organic solvent A is any one or both of tetrahydrofuran and N,N-dimethylformamide; In steps (2) and (3), organic solvent B is any one or both of methanol and dimethyl sulfoxide.
11. The method as described in claim 10, characterized in that, In steps (1) and (2), organic solvent A is tetrahydrofuran; in steps (2) and (3), organic solvent B is methanol.
12. The use of the composite material according to any one of claims 1-9 in the aerospace, automotive manufacturing, footwear and leather industry, and sports industry.
Citation Information
Patent Citations
Phenyloboricacid-modified cationic polymer and composite method and application thereof
CN101597349A
